Control of Glare for VDT Operators: Transmission of fluorescent light through UV filters and pink lenses - Mousa, G.Y (Canadian Journal of Optometry, 2021)
Since the introduction of video display terminals (VDTs) into offices, "glare" has become a source of patient complaints and a major triggering factor of migraine attacks among VDT users. Many patients are bothered by direct glare from fluorescent lamps or reflected glare from the surface of the screen. In order to reduce the impact of glare on VDT operators, some manufacturers have installed antiglare filters on the screen to reduce the reflective glare. Special luminaires with mirrored louvers directing the luminous flux downwards are recommended for lighting systems in VDT areas, but most offices are still illuminated by fluorescent lamp fittings not designed for this type of work.